Cortical Metabolic Activity Matches the Pattern of Visual Suppression in Strabismus - Adams, Daniel L. (Society for Neuroscience, 2013)
When an eye becomes deviated in early childhood, a person does not experience double vision, although the globes are aimed at different targets. The extra image is prevented from reaching perception in subjects with alternating exotropia by suppression of each eye's peripheral temporal retina. To test the impact of visual suppression on neuronal activity in primary (striate) visual cortex, the pattern of cytochrome oxidase (CO) staining was examined in four macaques raised with exotropia by disinserting the medial rectus muscles shortly following birth. No ocular dominance columns were visible in opercular cortex, where the central visual field is represented, indicating that signals coming from the central retina in each eye were perceived. However, the border strips at the edges of ocular dominance columns appeared pale, reflecting a loss of activity in binocular cells from disruption of fusion. In calcarine cortex, where the peripheral visual field is represented, there were alternating pale and dark bands resembling ocular dominance columns. To interpret the CO staining pattern, [(3)H]proline was injected into the right eye in two monkeys. In the right calcarine cortex, the pale CO columns matched the labeled proline columns of the right eye. In the left calcarine cortex, the pale CO columns overlapped the unlabeled columns of the left eye in the autoradiograph. Therefore, metabolic activity was reduced in the ipsilateral eye's ocular dominance columns which serve peripheral temporal retina, in a fashion consistent with the topographic organization of suppression scotomas in humans with exotropia.